TOPOISOMERASE INHIBITORS ACTIVITY OF YELLOW CHAMPAKA (MICHELIA CHAMPACA L.) BARK EXTRACTS AND FRACTIONS AND ITS LIRIODENINE CONTENTS - ZUHROTUN, ADE; HADISAPUTRI, YUNI ELSA; ALEXANDER, FREDERICK; SUSENO, RUDY; WICAKSONO, IMAM ADI (International Journal of Applied Pharmaceutics, 2022)
Objective: This research is aimed to investigate the activity of various extracts and fractions of yellow champaka (Michelia champaca L.) by mechanism-based yeast bioassay (MBYB) against the mutant yeasts. Liriodenin content, an active compound in M. champaca, will analyze to know the correlation with this assay. Methods: The bark of M. champaca was extracted by maceration and graded maceration using n-hexane, ethyl acetate, and methanol. The methanol extract was fractionated using water, n-hexane and ethyl acetate in the liquid-liquid extraction process. Each extract and fractions were tested in vitro by mechanism-based yeast bioassay for their topoisomerase inhibitor activity. Liriodenine content of all samples was analyzed by thin layer chromatography (TLC) densitometry method. Results: The yeast bioassay results showed that all extracts were active as topoisomerase inhibitors (IC12 values under 8000 µg/ml) except MGM. Liriodenine can be used as a marker of active compound in ethyl acetate samples that were EAM, EAGM and EAF with Pearson analysis value-0.887 (P=0.153) and these samples were relatively more active than others. Conclusion: This research showed that various extracts and fractions of yellow champaka bark have topoisomerase inhibitor's activity. Liriodenine can be used as a marker of the active compound so yellow champak bark is a potent natural agents for breast cancer.